Does living near hospital obscure the association between active living environments and hospitalization?. (May 2022) - Mah, Sarah M.; Herrmann, Thomas; Sanmartin, Claudia; Riva, Mylène; Dasgupta, Kaberi; Ross, Nancy A.
Abstract: Hospitals tend to be among the destinations that make densely populated, well-connected neighbourhoods more conducive to active living. In this study, we determined whether living near a hospital distorts the association between living in favourable ALEs and hospitalization for physical inactivity-related cardiometabolic diseases. We used a record linkage of 442, 345 respondents of the Canadian Community Health Survey and their hospitalization records for cardiometabolic disease. We then assessed respondents' neighbourhoods using the Canadian Active Living Environments measure (Can-ALE), a measure based on ≥3-way intersection density, residential density, and points of interest. We then calculated the distance in kilometers between the centroids of respondents' assigned dissemination areas and the nearest user-contributed location for hospitals from OpenStreetMap. We monitored changes in estimates for the association between ALEs and odds of cardiometabolic disease hospitalization using a series of logistic regressions with indicator variables for distances to hospital of 500 meters to 10 kilometers. We found that living between 500 meters and six kilometers of a hospital and was associated with modestly higher odds of cardiometabolic hospitalization (OR 1.10, 95% CI 1.02 to 1.18 for 500 meters; OR 1.05, 95% CI 1.01 to 1.09 for six kilometers). Living in more favourable ALEs was associated with lower odds of hospitalization (OR 0.79, 95% CI 0.68 to 0.91; comparing the most favourable to least favourable ALEs). Effect estimates between more favourable ALEs and lower odds of hospitalization were marginally strengthened when living within 2-6 kilometers to a hospital was accounted for. This study demonstrates the importance of disentangling interrelated geographic factors and underlines the potential for built environments to elicit reductions in health care. Highlights: Living within 6 km from hospital was associated with higher odds of hospitalization. Living in more favourable ALEs was associated with lower odds of hospitalization. Living close to hospital modestly attenuates the ALE-hospitalization relationship.